Study on Combustion Performance of a Diesel Engine Fueled by Synthesized Waste Cooking Oil Biodiesel Blends (Journal of University of Babylon for Engineering Sciences, 2018)
The waste cooking oil or used cooking oil is the best source of biodiesel synthesizing because it enters into the so-called W2E field, whereas not only get rid of the used cooking oils, but produce energy from the waste fuel. In this paper, biodiesel was synthesized from the used cooking oil and specifications are tested. From 1 liter of used cooking oil, 940 ml is gained. The remaining of a liter is glycerine and water. A Blend of 20% of biodiesel with 80% of net diesel by volume is formed. Blends of 100% diesel and 100% biodiesel are prepared too. The diesel engine combustion performance such as Brake thermal efficiency, brake specific fuel consumption, volumetric efficiency, mean effective pressure, and engine outlet temperature are studied in this paper. Cylinder pressure variation with crank angle is analyzed. The concentrations of hydrocarbon and nitrogen pollutants are measured. The results showed a significant enhancement in engine power and pollutant gases emitted. There is positive compatible with other critical researchers.